Behavior Sequence Analysis of Victims' Accounts of Intimate Partner Violence. Issue 21 (November 2022) - Keatley, D. A.; Quinn-Evans, L.; Joyce, T.; Richards, L.
Intimate partner violence (IPV) relates not only to physical forms of abuse, but also psychological, emotional, economic, and financial controlling behaviors. IPV is a dynamic, complex phenomenon that occurs over a relatively long period of time. While several measures of IPV exist, a method that can track the progression and escalation of such behaviors in relationships could offer more understanding and highlight key intervention points for individuals in such relationships. Behavior Sequence Analysis is used in the current research to map the chain and progression of behaviors in multiple real-world cases of IPV. Results indicate clear sequential clusters of behaviors such as physical and psychological abuse, and coercive controlling behaviors such as gaslighting, restricting movement, and removing freedoms. Overall, this research stands as a foundation framework to build a greater understanding of the processes and pathways of IPV, and offers workers in the field a novel method to assist with interviewing and intervening in such cases.